Non‐noble metal graphene oxide‐copper (II) ions hybrid electrodes for electrocatalytic hydrogen evolution reaction. Issue 2 (25th August 2015) - Muralikrishna, S.; Ravishankar, T.N.; Ramakrishnappa, T.; Nagaraju, D.H.; Krishna Pai, Ranjith
Abstract : Non‐noble metal and inexpensive graphene oxide‐copper (II) ions (GO‐Cu 2+ ) hybrid catalysts have been explored for the hydrogen evolution reaction (HER). We were able to tune the binding abilities of GO toward the Cu 2+ ions and hence their catalytic properties by altering the pH. We have utilized the oxygen functional moieties such as carboxylate, epoxide, and hydroxyl groups on the edge and basal planes of the GO for binding the Cu 2+ ions through dative bonds. The GO‐Cu 2+ hybrid materials were characterized by cyclic voltammetry in sodium acetate buffer solution. The morphology of the hybrid GO‐Cu 2+ was characterized by atomic force microscopy. The GO‐Cu 2+ hybrid electrodes show good electrocatalytic activity for HER with low overpotential in acidic solution. The Tafel slope for the GO‐Cu 2+ hybrid electrode implies that the primary discharge step is the rate determining step and HER proceed with Volmer step. © 2015 American Institute of Chemical Engineers Environ Prog, 35: 565–573, 2016